EKSPLORASI ETNOMATEMATIKA DALAM KEBUDAYAAN TUJUH LIKORAN DI DESA TEMPAPAN HULU KABUPATEN SAMBAS - Fitri, Indra; Sulisti, Hidayu (Math Educa Journal, 2024)
The purpose of this research is to find out how mathematical concepts are in the seven likoran night culture in Tempapan Hulu Village and their application in learning. This research used an ethnographic method, which was carried out in Tempapan Hulu Village, Sambas Regency. Research subjects were selected using purposive sampling technique. The instruments used are interviews, observation and documentation. The research results show that there are forms of objects that contain mathematical elements, such as the shape of coins that resembles a circle can be related to the concept of mathematics learning taught at school, such as the elements of a circle, and calculating the circumference and area of a circle. The concept of learning mathematics contained in pasung, glass, and candle cakes, namely, curved-sided spaces whose surface area and volume we can calculate. The shape of the plate contains the concept of learning mathematics, namely, the graph of the quadratic function. The mention of numbers by the Tempapan Hulu community in Likor contains the concept of numbers. Based on the results of research and discussion, it can be concluded that the tradition of the night of seven likoran has benefits in learning mathematics and plays an important role and provides insight into the study of science that can connect mathematical concepts in socio-cultural conditions in a community that has local wisdom value.